Jumbled Sentences to Improve Students’ Engagement in Learning English at SMA UII Yogyakarta - Chrisna, Gregorius Jhonathan Ariya; Pratiwi, Dwiyani (Formosa Journal of Sustainable Research, 2024)
The study seeks the effect of the jumbled sentence activity to improve students’ engagement in the classroom. The subject of this research were 29 students from the 11th grade science class at SMA UII Yogyakarta. This study was engaged using the Classroom Action Research method and conducted using the collaboration between the researcher and the teacher. The data gathered by observing using the observation checklist and giving the treatment to the students. The result of this study showed that the students’ engagement inside the classroom were increased after the activity. The result of the research also showed that the students’ responses (raising their hands, asking questions, answering questions, and initiating discussion) portray their improvement in their engagement after the treatment